A Numerical Algorithm for an Inverse Problem of a Partial Differential Equation with Multi-Parameter to Be Determined (Journal of Computational Mathematics, 1984)
A formulation of an inverse problem of a partial differential equation with multi-parameter to be determined is introduced. The numerical algorithm, pulse-spectrum technique, is extended to solve this type of inverse problem. An example for remote sensing of the thermal conductivity and specific heat of a nonhomogeneous material is demonstrated. Numerical simulations are carried out to test the feasibility and to study the general characteristics of this technique without real measurement data. It is found that the extended pulse-spectrum technique gives excellent results.